AKUNTABILITAS KINERJA PEGAWAI TERHADAP PELAYANAN PUBLIK PADA KANTOR KECAMATAN SANGATTA UTARA KABUPATEN KUTAI TIMUR - Rohandi Yusuf Palandrai Salasiah (ADMINISTRASI PUBLIK, 2017)
The Purpose of this research is to find out the factors that affect the implementation of the accountability employees performance in providing public services. To obtain the data authors do the research.     The results showed that the performance of a good officer and a good accountability process can be implemented. Then the last factor is the employment period. The presence of some employees with a relatively minimal working period makes the cause of the lack of understanding of the benefits of accountability to change the pattern of performance for the better. However, the existence of a workforce with experience of employee employment is considered much expected to guide employees who have a relatively minimal working period.     The need to increase understanding of the importance of accountability in an organization will be better if started early.In addition, socialization is required regularly to the performance patterns based on the principle of accountability that makes understanding of accountability can be improved along with the employment period of employment.